Enzyme–Catalysed Synthesis of Palm-Based Wax Esters-A Kinetic Study - Gunawan, Erin Ryantin; Basri, Mahiran; Suhendra, Dedy (Jurnal Natur Indonesia, 2011)
Wax esters are long chain esters that are derived from fatty acids and alcohols with chain lengths of 12 carbons or more. Wax esters havea wide range of application in industrial especially in cosmetics. The present work focuses on the synthesis of wax esters by alcoholysisreaction from palm oil and oleyl alcohol in hexane by lipase from Rhizomucor meihei (Lipozyme IM). Effect of various concentrations ofpalm oil and oleyl alcohol were studied to deduce the kinetics and mechanism of the reaction. The alcoholysis reaction followed Michaelis-Menten kinetics. The reaction follows a Ping-pong Bi-Bi mechanism. The maximum rate was estimated to be 6 x 10 -3 mmol/h. mg catalystand the Michaelis-Menten constant for palm oil and oleyl alcohol were 4.145 M and 6.120 M, respectively.